Prospective Study of Perioperative Circulating Tumor DNA Dynamics in Patients Undergoing Hepatectomy for Colorectal Liver Metastases. Issue 5 (6th May 2023) - Newhook, Timothy E.; Overman, Michael J.; Chun, Yun Shin; Dasari, Arvind; Tzeng, Ching-Wei D.; Cao, Hop S. Tran; Raymond, Victoria; Parseghian, Christine; Johnson, Benny; Nishioka, Yujiro; Kawaguchi, Yoshikuni; Uppal, Abhineet; et al.
Abstract : Objective: To evaluate the association of perioperative ctDNA dynamics on outcomes after hepatectomy for CLM. Summary Background Data: Prognostication is imprecise for patients undergoing hepatectomy for CLM, and ctDNA is a promising biomarker. However, clinical implications of perioperative ctDNA dynamics are not well established. Methods: Patients underwent curative-intent hepatectomy after preoperative chemotherapy for CLM (2013–2017) with paired prehepatectomy/postoperative ctDNA analyses via plasma-only assay. Positivity was determined using a proprietary variant classifier. Primary endpoint was recurrence-free survival (RFS). Median follow-up was 55 months. Results: Forty-eight patients were included. ctDNA was detected before and after surgery (ctDNA+/+) in 14 (29%), before but not after surgery (ctDNA+/−) in 19 (40%), and not at all (ctDNA−/−) in 11 (23%). Adverse tissue somatic mutations were detected in TP53 (n = 26; 54%), RAS (n = 23; 48%), SMAD4 (n = 5; 10%), FBXW7 (n = 3; 6%), and BRAF (n = 2; 4%). ctDNA+/+ was associated with worse RFS (median: ctDNA+/+, 6.0 months; ctDNA+/−, not reached; ctDNA−/−, 33.0 months; P = 0.001). Compared to ctDNA+/+, ctDNA+/− was associated with improved RFS [hazard ratio (HR) 0.24 (95% confidence interval (CI) 0.1–0.58)] and overall survival [HR 0.24 (95% CI 0.08–0.74)]. Adverse somatic mutations were not associated with survival. After adjustment for prehepatectomy chemotherapy, synchronous disease, and ≥2 CLM, ctDNA+/− and ctDNA−/− were independently associated with improved RFS compared to ctDNA+/+ (ctDNA+/−: HR 0.21, 95% CI 0.08–0.53; ctDNA−/−: HR 0.21, 95% CI 0.08–0.56). Conclusions: Perioperative ctDNA dynamics are associated with survival, identify patients with high recurrence risk, and may be used to guide treatment decisions and surveillance after hepatectomy for patients with CLM.